International Legal Framework Effects on International Law and especially its Impact on the Environment Law - Mozes, Sapard Vincent-de Paul (European Journal of Applied Sciences, 2022)
In order for the rule of law to accomplish its main objectives or goals, which involves safeguarding people's freedom and well-being, international law must be utilized. The peculiar aspects of international law and the global legal system do not destruct the rule of law in any way. International law does not contain anything inherent towards the rule of law obstruction. The law plays a fundamental role in improving and promoting the rule of law. This paper focuses on the various international legal frameworks and their effects on general law and the environment. The international legal framework has had adverse impacts on various sectors such as health and human right in the different states in the world. The article investigated various problems such as how to have the international legal frameworks impacted the various sectors in the states worldwide, what impactt has the frameworks had on the environment itself, and how the countries have benefited from the international law. The findings of this paper have concluded that these legal frameworks on human rights have affected the general international law in various ways. These frameworks have had a significant role in enhancing the promotion and solidification of the global language of human rights law in the local discussion. In the health sector, the development and explanation of global health law over the past twenty years has been a recognizable development in international health policy mostlyin this period of COVID-19. In the past, public health was considered as a domain of nearly obsolete national jurisdiction, and multilateral relationships in this sphere were narrowed to discrete regions. The international environmental law sector has developed into a distinct part of international law besides its gradual start. Currently, it is full of principles and standards that regulate and control environmental aspects. The principles are significant for several reasons, such as enhancing a platform to dialogue the new environmental conventions and treaties and adopt the ones that are in existence to save the world as united and unique entity.